2016
DOI: 10.2152/jmi.63.140
|View full text |Cite
|
Sign up to set email alerts
|

Early combined treatment with steroid and immunoglobulin is effective for serious Kawasaki disease complicated by myocarditis and encephalopathy

Abstract: Severe-type Kawasaki disease (KD) complicated by serious myocarditis and encephalopathy can be successfully treated without abnormality of the coronary arteries by steroid pulse treatment and intravenous immunoglobulin (IVIg). A 4-year-old Japanese girl was diagnosed with KD due to a 6-day history of fever, rash, flushed lips, conjunctival hyperemia, palmar edema, and cervical lymphadenopathy. The day after initiation of IVIg and aspirin, cardiac gallop rhythm was identified. Cardiac ultrasonography revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…4,5,[9][10][11]18 Some authors have reported IVMP as a rescue therapy in children with refractory KD who had myocarditis and symptomatic congestive heart failure during the acute stage of the disease. [19][20][21] Some studies have shown that 51%-80% of patients with MIS-C did not respond to IVIG treatment, 6,10 while 70% of our patients with MIS-C appear to be unresponsive to IVIG. CS was added to this group's therapy on day 3 on average.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…4,5,[9][10][11]18 Some authors have reported IVMP as a rescue therapy in children with refractory KD who had myocarditis and symptomatic congestive heart failure during the acute stage of the disease. [19][20][21] Some studies have shown that 51%-80% of patients with MIS-C did not respond to IVIG treatment, 6,10 while 70% of our patients with MIS-C appear to be unresponsive to IVIG. CS was added to this group's therapy on day 3 on average.…”
Section: Discussionmentioning
confidence: 62%
“… 4 , 5 , 9 11 , 18 Some authors have reported IVMP as a rescue therapy in children with refractory KD who had myocarditis and symptomatic congestive heart failure during the acute stage of the disease. 19 21 …”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease (KD) is a rare pediatric systemic vasculitis that typically affects medium-sized arteries, particularly the coronary arteries. The disorder was first described by pediatrician Tomisaku Kawasaki in Japan in 1967 [ 19 ]. In developed countries, Kawasaki disease is the leading cause of acquired heart disease.…”
Section: Comparison Of Mis-c With Kawasaki Diseasementioning
confidence: 99%
“…Classically, diagnosis of KD is based on clinical criteria represented by persistent fever for five or more days with at least four of five main clinical features, which tend to appear sequentially: bilateral nonexudative conjunctivitis, erythema of the lips and oral mucosa, polymorphous rash, cervical lymphadenopathy, and abnormalities of hands and feet, including also perineal erythema ( Table 1 ) [ 5 ]. Typically, all these clinical features are not present at the time of fever onset.…”
Section: Introductionmentioning
confidence: 99%